Contribuição ao estudo do desgaste de bedames na usinagem de ligas de alumínio-silício - Silva, Edson Roberto da [UNESP] (2015)
This research aims to monitoring the tool wear when turning aluminum-silicon alloys. The specific goal is to turn channels in automotive pistons with two different chemical compositions by checking the influence of the control factors cutting speed (v c ), tool feed (f) and workpiece silicon content on response N-Class chisel life. As well as to study the effect of the same aforementioned variables on channels productivity. A turning center Romi GL-240M was used. 0.3 mm flank wear was adopted as a criterion of tool life. Chisel flank wear was monitored and measured by using a stereo-microscope Zeiss Discovery V8. Analysis of Variance (ANOVA) was used to quantify statistical influences of the control factors upon response. Adhesion and abrasion of the part material over tools were observed. Silicon content was the most influential factor on the channels productivity so that the lower silicon content, the greater tool productivity. Cutting speed and tool feed has influenced on channels productivity strongly. The first one is inversely proportional to tool life whereas the latter is directly proportional to channels productivity